Influencing Factors of BIM Application Benefits in Construction Projects Based on SEM - Chi Zhang; Wanqiang Dong; Wei Shen; You Du (Buildings)
Facing the challenges of high complexity in Building Information Modeling (BIM) technology application and insufficient realization of its benefits, this study identifies key influencing factors of BIM effectiveness through the literature analysis and multi-case research. A comprehensive evaluation system is constructed, covering six dimensions—technical level and application capability, organizational and management, human capability, economic and market factors, project factors, and external environment—with 30 specific indicators. Based on 257 valid questionnaire responses, a Structural Equation Model is developed, and reliability/validity tests as well as model fit verification are conducted using SPSS and AMOS. The findings reveal that human capability factors (weight: 0.182) serve as the core driver for realizing BIM value. Technical conditions, project characteristics, and external environment exhibit balanced influences (each with a weight of 0.164), while economic market (weight: 0.167) and organizational management (weight: 0.159) require collaborative optimization to enhance synergy. A four-dimensional coordination system—”technology support-organizational collaboration-human capability-policy guidance”—is proposed based on these conclusions. Practical application demonstrates that this system improves BIM implementation efficiency by 23% and reduces project rework rates by 40%, providing quantifiable implementation pathways for construction enterprises to optimize resource allocation and advance digital transformation. The research aims to offer theoretical guidance and technical support for promoting the digital evolution of the construction industry.